Anthropometric indicators as predictors of high blood pressure among the Ao tribe of North-East India - Maken, Temsutola; Varte, Lalmunlien Robert (Asian Journal of Medical Sciences, 2013)
Objective: Hypertension is related to increased body fat, which can be evaluated by anthropometric indicators among the Aos, a tribe of North-East India. Methods: Cross-sectional study with a sample of 1804 Ao adults (male= 890) (females= 914) aged 18 to 70 years. We considered the following anthropometric indicators: body mass index, waist circumference, waist-tohip ratio and waist-to-stature ratio. To identify predictors of high blood pressure, we adopted the analysis of receiver operating characteristic curves with a confidence interval of 95%. Result: For males, the area under curve with confidence intervals were BMI = 0.691 (0.67-0.712); waist circumference=0.757 (0.739-0.775); waist-to-hip ratio=0.692 (0.671-0.713); waist-to-stature ratio = 0.763 (0.745-0.781) and Conicity index = 0.734 (0.716-0.716). For females, the values were BMI = 0.754 (0.732-0.776); waist circumference = 0.762 (0.74-0.784); waist-to-hip ratio = 0.690 (0.668-0.784), waist-to-stature ratio=0.776 (0.753-0.799) and Conicity index=0.722 (0.701-0.743). Different cut off points of anthropometric indicators with better predictive power and their relevant sensitivities and specificities were identified. Conclusion: BMI does not show a very good area under the ROC curve. It seems that waist-to-stature ratio is the best predictor, followed by waist circumference and Conicity index among the males and results in high sensitivity and specificity to hypertension. We suggest the use of both waistto- stature ratio and waist circumference to predict hypertension among males. Among females, waist-to-stature ratio is the best predictor, followed by waist circumference and body mass index. DOI: http://dx.doi.org/10.3126/ajms.v4i3.6275 Asian Journal of Medical Sciences 4(2013) 15-22